Pemberdayaan UMKM Melalui Layanan Tamades Pada PT BPR BKK Karangmalang (Perseroda) Kabupaten Sragen - Jesicha Mutiara Dewi; Fitri Rohmadzany; Jaryanto Jaryanto (Pusat Riset dan Inovasi Nasional, 2024)
Fundraising strategies implemented by financial institutions are currently increasingly diverse. This collection is carried out to increase the value of customer transactions and increase customer interest in using products offered by financial institutions, especially BPRs. Banking conducts promotions to the public to introduce its various products either through existing media or by providing benefits such as rewards to customers. In addition, to attract customers, the bank provides the best service, both in excellent service, guaranteed security of funds deposited by customers, interest rates according to customer needs, and a variety of products. The method used in this research is descriptive method. With data obtained from observation and interviews with employees and customers of PT. BPR BKK Karangmalang. PT. BPR Karangmalang has superior products, namely products that are most in demand by customers, especially MSME players. This product is a type of third party fundraising product known as Tamades. This Tamades service provides many advantages for MSME players to deposit their funds, because interest rates are very favorable for third parties, good service, easy procedures for making Tamades, and other benefits for customers.